Valuing local manufacturing technology: a technology acquirer's perspective - Abd Rahman, Azmawani; Loke, Chuen Chiat (IEEE, 2014)
This study investigates the valuation of Malaysian manufacturers towards local and imported manufacturing technology. The eight technology attributes namely the technology acquisition cost, functionality, quality, usability, flexibility, maintenance, vendor-customer relationship and technology scale were used as dimensions to measure the technology valuation. Result indicated that there exist significant differences on perception of technology attributes between the local and imported technology. Respondents in this study valued imported technology as better than the local in terms of cost, maintenance, vendor customer relationship and technology scale. This study however found that respondents valued local and imported manufacturing technology as similar in terms of functionality, quality, usability, and flexibility. Implication for both theory and practiced were discussed.